2018
DOI: 10.1177/1708538118818622
|View full text |Cite
|
Sign up to set email alerts
|

Anti-platelet and anti-coagulant therapy in peripheral arterial disease prior to surgical intervention

Abstract: Objective Peripheral artery disease is a major clinical co-morbidity that can significantly affect quality of life, especially in the presence of diabetes mellitus and older age. The focus of this literature review is on medical management, through anti-platelet and anti-coagulation, of peripheral artery disease prior to undergoing surgical or endovascular management. Method Extensive electronic literature search performed in four major databases (PubMed, SCOPUD, Embase and Ovid) to identify the published rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…3 Similar to age and diabetes mellitus (DM), hyperlipidemia is one of the known risk factors of atherosclerosis. 4 Increased triglyceride (TG) and decreased high density lipoprotein cholesterol (HDL-C) values increase atherosclerosis risk. With regard to this information, TG/HDL-C ratio is used as the atherogenic index.…”
Section: Introductionmentioning
confidence: 99%
“…3 Similar to age and diabetes mellitus (DM), hyperlipidemia is one of the known risk factors of atherosclerosis. 4 Increased triglyceride (TG) and decreased high density lipoprotein cholesterol (HDL-C) values increase atherosclerosis risk. With regard to this information, TG/HDL-C ratio is used as the atherogenic index.…”
Section: Introductionmentioning
confidence: 99%
“…15 As peripheral artery disease is a complex condition, Harky et al shown that anticoagulant therapy is paramount to preventing disease. 16 Several observatories report that the global outbreak of coronavirus disease 2019 (COVID-19) is a hypercoagulable disorder. 17 A retrospective multicenter cohort study about COVID-19 shown that the potential risk factors of older age, high SOFA score, and d-dimer greater than 1mg/mL may have a poor prognosis at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…15 As peripheral artery disease is a complex condition, Harky et al shown that anticoagulant therapy is paramount to preventing disease. 16…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic heart disease is a leading cause of morbidity and mortality worldwide (1). Anti-thrombotic therapy and intervention are the main strategies to protect cardiomyocytes against hypoxia-induced damage (2).…”
Section: Introductionmentioning
confidence: 99%